The Prohibition of Civil Servant (ASN) in Actions to Benefit Prospective of Regional Head in Public - M Hary Rubianto; Ardiansyah Ardiansyah; Bagio Kadaryanto (Jurnal Daulat Hukum, 2022)
This research aims to understand the correlation between ASN and Regional Head Election (Pilkada) as election for choose leader by democratic based on principle of direct, general, free, confidential, honest and fair which submitted by party political or combined party political. About implementation, right choose of Civil Servant or abbreviated with ASN prohibited to declare openly to public to invite choose one of candidate so that tend becomes form "campaign" or endorsement. However thus, level violation to implementation Pilkada simultaneously which ruled by government. This research used Socio Legal Research on phenomenon law which there is in public election and approach problem used a case approach. The conclusion show that the implementation of the banning the ASN in Bengkalis on Regional Head Candidates 2020 not yet done with good. Because still many found ASN which no neutral. It is caused the existence connection family Among ASN with candidate regional head, ambition of career position, no clear dan nothing strictly rules, weakness enforcement law.